Clinicopathological and 123I‐FP‐CIT SPECT correlations in patients with dementia. Issue 3 (24th January 2018) - Jung, Youngsin; Jordan, Lennon G.; Lowe, Val J.; Kantarci, Kejal; Parisi, Joseph E.; Dickson, Dennis W.; Murray, Melissa E.; Reichard, Ross R.; Ferman, Tanis J.; Jones, David T.; Graff‐Radford, Jonathan; Savica, Rodolfo; et al.
Abstract: The relationship between clinicopathologic diagnosis and 123 I‐FP‐CIT SPECT in 18 patients with dementia (12 with Lewy body disease) from one center in the United States was assessed. The sensitivity and specificity of abnormal 123 I‐FP‐CIT SPECT with reduced striatal uptake on visual inspection for predicting Lewy body disease were 91.7% and 83.3%, respectively. The mean calculated putamen to occipital ratio (mPOR) based on regions of interest was significantly reduced in Lewy body disease compared to non‐Lewy body disease cases ( P = 0.002). In this study, abnormal 123 I‐FP‐CIT SPECT was strongly associated with underlying Lewy body disease pathology, supporting the utility of 123 I‐FP‐CIT SPECT in the clinical diagnosis of dementia with Lewy bodies.